2014
DOI: 10.1371/journal.pone.0110275
|View full text |Cite
|
Sign up to set email alerts
|

Lycium barbarum Polysaccharides Protect Human Lens Epithelial Cells against Oxidative Stress–Induced Apoptosis and Senescence

Abstract: ObjectivesWe aimed to investigate the protective effect of Lycium barbarum polysaccharides (LBPs) against oxidative stress–induced apoptosis and senescence in human lens epithelial cells.MethodsTo study apoptosis, SRA01/04 cells, a human lens epithelial cell lines, were exposed to 200 µM hydrogen peroxide (H2O2) for 24 h with or without pretreatment with LBPs. Cell viability was measured using a Cell Counting Kit-8 (CCK-8) assay. Cell apoptosis, intracellular reactive oxygen species (ROS), and the loss of mito… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
37
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(40 citation statements)
references
References 50 publications
3
37
0
Order By: Relevance
“…Meanwhile, alterations of those proteins were mitigated by LBPs, which illustrated LBPs reduced apoptosis through repressing the intrinsic apoptosis pathway in PC-12 cells. The anti-apoptotic role of LBPs in H 2 O 2 -induced PC-12 cells was coincident with that in human lens epithelial cells [32].…”
Section: Discussionsupporting
confidence: 57%
“…Meanwhile, alterations of those proteins were mitigated by LBPs, which illustrated LBPs reduced apoptosis through repressing the intrinsic apoptosis pathway in PC-12 cells. The anti-apoptotic role of LBPs in H 2 O 2 -induced PC-12 cells was coincident with that in human lens epithelial cells [32].…”
Section: Discussionsupporting
confidence: 57%
“…12 A bunch of studies has shown that LBP has various bioactivities as well as antioxidant characteristics. LBP is also considered to have protective effects on lens epithelial cells 18 and myocardial cells. This effect is likely to be correlated with its antioxidant effect and we hypothesized that LBP treatment could protect the osteoblast from the stress.…”
Section: Discussionmentioning
confidence: 99%
“…After 5 h incubation at 37°C, Cis and Mir + Cis cells were exposed to 10 μM cisplatin for 24h, other cells did not expose to cisplatin. 14 Then the medium was removed and added 100 μL fresh medium containing 10% CCK-8 (Dojindo, Kumamoto, Japan) to each well. The plate was incubated for 1-4 hours, and the absorbance at 450 nm was determined using a microplate reader (Thermo Fisher Scientific, Waltham, MA, USA).…”
Section: Cell Proliferation Was Detected By Cell Counting Kits-8 (Cckmentioning
confidence: 99%